MODEL PEMBELAJARAN KOLABORATIF DAN KREATIF UNTUK MENGHADAPI TUNTUTAN ERA REVOLUSI INDUSTRI 4.0 - Koko Adya Winata (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2020)
This paper examines how learning models should be applied in schools to respond to the demands of the era of the industrial revolution 4.0 which has become a necessity. The industrial revolution 4.0 is an era that shows the rapid development of technology and has caused many jobs in the past to be distorted. The role of humans is taken over step by step by automatic machines, as a result the number of unemployment is increasing. In order to avoid the negative impact of the industrial revolution 4.0, educational institutions must be able to answer these challenges by selecting and applying learning models in schools that provide the skills or skills needed. The demand for skills that can answer the challenges of the 4.0 revolution era, must be prepared through a directed and comprehensive learning plan. This means that the learning process does not only think and move towards the academic dimension. In the learning process, often students are only prepared to have intellectual intelligence and very little learning gives equal opportunities to students to hone other intelligence. At the same time the learning method is more dominated by the authority of the teacher which is very central and rigid, while the students are positioned as objects that must accept what is presented by the teacher. As a result, students do not have the ability to develop their creativity and potential. Learning models that can answer the challenges of the revolution era 4.0 are collaborative and creative learning models. Through collaborative and creative learning, students are directed to be able to develop their potential and hone their creative thinking skills. The collaborative and creative learning model makes it easy for students to learn and work together and learn to solve problems together. Creative thinking to solve existing problems is a learning process needed to answer the challenges of the industrial revolution 4.0.